Analisis Strategi Pengembangan Pasar dalam Industri Pariwisata - Donny Juliandri Prihadi,; Maryam Salampessy,; Verina Wijaya,; Erris Kusumawidjaya,; Christy Widyawati, (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
The purpose of this study is to analyze and determine market development strategies in the tourism industry. This research approach collects data through literature studies, which involve reading literature from various sources including books, journals and reports using qualitative and deductive approaches. The findings in this study are that there are strategies for developing facilities and infrastructure to support the tourism industry, namely the strategy for developing local community-based accommodation, and the strategy for developing supporting facilities with the concept of an agropolitan area, including restaurant or food stall facilities, ATM facilities, and rest areas. In addition, there are also market development strategies in the tourism industry, including market segmentation, use of technology, collaboration with stakeholders, product innovation, and sustainability.